“It Takes a Village to Raise a Child” -Who and What to Consider in Designing Parental Mediation Features? - Valença, George; Assis, João Victor; de Mello, Maria Góes (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2025)
Introduction: The pandemic intensified children’s use of connected devices, especially social media apps. The 2024 TIC Kids survey shows that over 60% of children aged 9–12 have profiles on these platforms (despite being under the minimum age of 13). This exposes them to risks like privacy loss, inappropriate content, and commercial exploitation. Objective: We aim to understand the main recommendations to design parental mediation and control features arising from the public consultation on platform regulation by CGI.br. Methodology or Steps: We analyzed the contributions on parental mediation regulations through thematic synthesis. Results: Based on this, we derived early requirements and evaluated TikTok and Instagram on these requirements.